Tuning coiled coil stability with histidine-metal coordination. Issue 48 (30th November 2018) - Tunn, Isabell; de Léon, Alberto S.; Blank, Kerstin G.; Harrington, Matthew J.
Abstract : Reinforcing coiled coils with histidine-metal coordination reversibly increases their thermodynamic and mechanical stability with implications for biomimetic hydrogel design. Abstract : Coiled coils (CCs) have emerged as versatile building blocks for the synthesis of nanostructures, drug delivery systems and biomimetic hydrogels. Bioengineering metal coordination sites into the terminal ends of a synthetic coiled coil (CC), we generate a nanoscale biological building block with tunable stability. The reversible coordination of Ni 2+ thermodynamically stabilizes the CC, as shown with circular dichroism spectroscopy. Using atomic force microscopy-based single-molecule force spectroscopy, it is further shown that Ni 2+ -binding reinforces the CC mechanically, increasing the barrier height for dissociation. When used as a dynamic crosslink in polyethyleneglycol-based hydrogels, the single-molecule stability of the CC is directly transferred to the bulk material and determines its viscoelastic properties. This reversibly tunable CC, thus, highlights an effective strategy for rationally engineering the single-molecule properties of biomolecular building blocks, which can be translated to the emergent properties of biomimetic materials, as well as other CC containing molecular assemblies.